Kebijakan Sektor Pertanian sebagai Awal Kebangkitan Ekonomi (Studi Kasus Taiwan Dalam Mengelola Komoditas Padi) - Deni Danial Kesa; Cheng-Wen Lee (Program Pendidikan Vokasi Universitas Indonesia, 2013)
ABSTRACT. Indonesian agricultural has big potential to developed, but in fact most of our farmers are stillmany who are categorized as poor. Looking at Taiwan 's success in fostering innovation and empoweragricultural resources , much can be learned in a production system . The policy implemented by the Ministry ofagriculture and all stakeholders in Taiwan. For future prospects Indonesia, as applicable steps and futureprospects, which should be applied in the rice production system in Indonesia such as maximizing theproduction of rice, with a maximum cost. Self-sufficiency for rice as staple food is main agenda for government, with expanding farmers rice fields in several potential areas and supported by the principle of conservationprinciples. Distribution of development agriculture particularly rice, should be offset consistent development ofintegrated technologies . Quantity must be short-term targets, with diversified land and production quality useunfettered access to farmers' access to protection in aspects of management, availability of equipment , andKebijakan Sektor Pertanian sebagai Awal Kebangkitan Ekonomi (Studi Kasus Taiwan Dalam Mengelola Komoditas Padi)Deni Danial Kesa, Cheng-Wen LeeVolume 1, Nomor 1, pp 44-7345impartial subsidies in accordance with applicable regulations . Policy implementation should be consistent withthe applicable law and Indonesian agricultural development strategic plan together with all stakeholders.Keywords : Agricultural Sector Policy , the rice supply chain , diversification